Modern Accounting Research: History, Survey, and Guide (Book). - Hendrickson, Harvey S.; Chow, Chee W. (The Accounting Review, 1985)
Abstract Reviews the book "Modern Accounting Research: History, Survey, and Guide," by Richard Mattessich.